2019
DOI: 10.1038/s41467-019-09382-9
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal mGluR-mediated synaptic plasticity and autism-like behaviours in Gprasp2 mutant mice

Abstract: Autism spectrum disorder (ASD) is characterized by dysfunction in social interactions, stereotypical behaviours and high co-morbidity with intellectual disability. A variety of syndromic and non-syndromic neurodevelopmental disorders have been connected to alterations in metabotropic glutamate receptor (mGluR) signalling. These receptors contribute to synaptic plasticity, spine maturation and circuit development. Here, we investigate the physiological role of Gprasp2 , a gene linked to n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 58 publications
(72 reference statements)
1
33
0
Order By: Relevance
“…mGluR5 function may be similarly affected in PV-Lmo4KO mice. Altered mGluR5 function has been associated with autism-like behaviors in mice lacking Gprasp2 43 . Moreover, PV neuron-specific ablation of mGluR5 induces social novelty deficits and compulsive repetitive behaviors associated with loss of PV neurons and reduced inhibitory currents (mIPSC) at the hippocampus 44 .…”
Section: Discussionmentioning
confidence: 99%
“…mGluR5 function may be similarly affected in PV-Lmo4KO mice. Altered mGluR5 function has been associated with autism-like behaviors in mice lacking Gprasp2 43 . Moreover, PV neuron-specific ablation of mGluR5 induces social novelty deficits and compulsive repetitive behaviors associated with loss of PV neurons and reduced inhibitory currents (mIPSC) at the hippocampus 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies in humans and animal models have revealed aberrations in dendritic spine architecture in several psychiatric disorders including depression and others related to stress (Edfawy et al, 2019;Guo et al, 2019;Yang et al, 2020). Changes in spine density and organization are thought to contribute to the behavioral disorder caused by stress exposure (Chen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Detailed methods for behavioral tests, electrophysiology recordings, neuronal labeling with AAV, and confocal imaging, preparation of RNA and DNA samples, RNAseq, methylation assays, qRT-PCR, immunofluorescence, and tissue dissection methodologies were performed as previously described [ 17 19 ] and are provided as Supplementary materials and methods .…”
Section: Methodsmentioning
confidence: 99%
“…We chose to investigate the mPFC since this region is: (1) strongly targeted by the glucocorticoid system [8], (2) responsible for top-down control of other brain systems according to the animals' internal state and intention [22], and (3) has been strongly implicated in the regulation of social hierarchy behaviors [6]. To investigate neuronal morphology changes in ELS mice, we performed peripheral injection of adeno-associated viral particles containing a GFP construct (AAV9.hSyn.GFP) via the tail vein to achieve a Golgi-like labeling of neurons in the whole mouse brain (see "Materials and methods" section and [17]). We then performed a reconstruction of neurons using confocal microscopy and assessed neuronal arborization and complexity via Sholl analysis.…”
Section: Faster Resolution Of Social Conflicts In Animals That Experimentioning
confidence: 99%